Book Review: In the Footsteps of Ethel Benjamin by Janet November - Morris, Caroline (Victoria University of Wellington Law Review, 2010)
This article is a book review of Janet November In the footsteps of Ethel Benjamin, New Zealand's first woman lawyer (Victoria University Press / Law Foundation, Wellington, 2009) 260 + xi pages, $50. Morris describes the book as the biography of a remarkable woman who was not only the first woman lawyer in New Zealand, but also a "poster girl" for proponents of opening up the legal profession to women in England. Morris notes that Benjamin's achievements still remind the reader of the work that needs to be done for women in law. However, the private life of Benjamin is difficult to decipher from this book due to a lack of private papers kept by Benjamin. The article concludes that in Janet November's book, we have a fitting testament to the achievements and legacy of Ethel Benjamin.